The Memory of Clothes - Gibson, Robyn (Springer, 2016)
Once hanging static in a wardrobe or folded away in a trunk, in recent times clothes have found themselves thrown into the spotlight. The crowds that are drawn to large scale fashion exhibitions staged with increasing frequency in galleries and museums around the world offer glimpses into the meaning that we attach to these items of clothing. Apart from their aesthetic value, clothes have the ability to evoke issues of identity, of the relation of self to body and self to the world. We are able to find ourselves through the experiences of delving into our wardrobes and remembering. Clothes are thus layered with meaning since they have the power to act as memory prompts. Woven into their fabric are traces of past experiences; stitched into their seams are links to people we have loved and lost. Viewed as visual objects, clothing is not frivolous, flippant or foolish. In telling and talking about clothes, we reveal much about ourselves, our lives and the experiences that we drape around our bodies. Whether bought or handmade, passed down or reconstructed, clothes help us to construct meaning as we remember those things in our lives that matter.